PENYULUHAN PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN SATU HALAMAN MENUJU KEMASLAHATAN MANUSIA - K Anom W; Fuad Abd Rachman; Jejem Mujamil S; Sanjaya sanjaya; Eka Ad'hiya (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Based on the situation analysis, the formulation of the problem is how to equip the ability, knowledge, and skills of Compiling One Page RPP for chemistry teachers in Sekayu City, South Sumatra and Chemical Education students, FKIP Sriwijaya University. Service activities are carried out by providing counseling for chemistry teachers and village lectures for students, preparing a Chemistry Learning Implementation Plan. The purpose of this service is to prepare an example of an integrated high school and vocational high school chemistry learning program plan with PBL, Project, or STEM models. This service activity is beneficial for teachers and students to the community through chemistry. 14 Sekayu City chemistry teachers and 8 chemistry students are the target audience for this community service activity. The target of dedication was achieved, from the results of the evaluation of the activities of each target audience, they compiled an example of a One-Page Learning Implementation Plan. The Learning Implementation Plan has the nuances of chemistry teachers and students close to the daily activities of the community. Suggestions from this community service activity are that the target audience can socialize and implement this One Page Learning Implementation Plan in their respective schools.